Classicising crisis : the modern age of revolutions and the Greco-Roman repertoire - Goff, Barbara E.; Simpson, Michael, 1957- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Geopolitical shifts and economic shocks, from the early modern period to the 20th century, were frequently represented in terms of classical antecedents. In this book an international team of contributors - working across classics, history, politics, and English - address a range of revolutionary transformations in England, America, France, Italy, and Russia, all of which were accorded the classical treatment. The chapters investigate discrete cases of classicising crisis, while the introduction highlights patterns among these moments. Underlying the collection is the critical premise that the association of revolutions with the Greco-Roman classics, otherwise quite conventional and familiar, may itself involve an epistemic 'crisis', as these terms are alien to one another, antagonistic, and yoked together in a violent blending of ancient and modern. Classicising crisis: the modern age of revolutions and the Greco-Roman repertoire is essential reading for students and scholars of classical reception and classicism, and will also be of interest to researchers in related subjects"--
Introduction Barbara Goff and Michael Simpson1. 'Innovation' and revolution in seventeenth-century England Rachel Foxley2. Classicising the American Crisis, 1760-1789 Nicholas Cole3. Virtue, Representation, and the Politics of Ancient Greek History during the 1790s in Britain Sebastian Robins4. The Night of the Statues: revolution and classicism in Alejo Carpentier's The Kingdom of this World Adam Lecznar5. Classicising The Woman Question in Nineteenth-Century Greece Katerina Kitsi-Mitakou and Vasiliki Misiou6. 'What's the Roman Republic to me, or I to the Roman Republic?': Victorian Classicism and the Italian Risorgimento Isobel Hurst7. Classics, Crisis and the Soviet Experiment to 1939 Henry Stead and Hanna Paulouskaya8. Seeking New Classics in a Crisis: Modernity as Ancient History in German Thought Benjamin Gray9. Of Minotaurs and Macroeconomics: Greek myth and common currency Michael Simpson.Index
OCLC-licensed vendor bibliographic record.
Keywords: Civilization, Western -- Classical influences; Civilization, Modern -- Classical influences; Civilization, Classical -- Influence; Revolutions -- History; Civilization, Classical -- Study and teaching; Classicism -- History; HISTORY / Ancient / General